Game-changer in the fight against Huntington's disease: Cholesterol nanoparticles restore brain function in mice - Martín, Mauricio Gerardo (2023)
Huntington's Disease (HD) is a devastating neurodegenerative disorder characterized by progressive cognitive and motor impairment. Multiple studies have shown impaired cholesterol biosynthesis in the brains of HD patients and various rodent models and different strategies have explored to which extent modulation of brain cholesterol levels could be beneficial for HD cognitive and motor deficits. The work titled "Chronic cholesterol administration to the brain supports complete and long-lasting cognitive and motor amelioration in Huntington's disease" by Birolini et al. is the culmination of 25 years of effort by Elena Cattaneo's research group in this area...